Working conditions, career barriers and perceived equity among neuro-oncology professionals: insights from the Japan society for neuro-oncology (JSNO) gender equality and diversity committee survey - Akiko Higuchi; Kaoru Tamura; Yuko Watanabe; Tatsuya Abe; Mitsutoshi Nakada; Shota Tanaka; Yoshiko Okita; Motoo Nagane; Yuichi Hirose; Takamitsu Fujimaki; on behalf of The Gender Equality and Diversity Committee of the Japan Society for Neuro-Oncology (International Journal of Clinical Oncology, 2026)
Abstract Background Gender equity, work-life balance, and career development have become important concerns in the medical profession. However, empirical evidence on how neuro-oncology professionals experience working conditions, career barriers, and perceived inequity remains limited. Methods We conducted a nationwide, cross-sectional, anonymous online survey of members of the Japan Society for Neuro-Oncology (JSNO) to evaluate working conditions, career-related concerns, job satisfaction, perceived workplace discrimination, and organizational challenges. Results Among 292 respondents (response rate, 35.9%), the mean weekly working time was 56.7 h, and 45.5% worked ≥ 60 h per week. Women were markedly underrepresented in managerial/leadership positions (6.7% vs. 47.3%) and were more likely to hold part-time positions. Multivariable logistic regression analysis showed that female sex was independently associated with greater perceived workplace discrimination (OR 2.71, 95% CI [1.23–5.98], p = 0.013), after adjustment for working hours, caregiving experience, and managerial/leadership position. An age-by sex interaction was observed for career-related concerns: these increased with age among women but decreased among men. Longer working hours were associated with lower satisfaction with income, working hours, and work-life balance. Although workplace support systems are widely available, substantial perceptual gaps and workload redistribution challenges were identified. Conclusion These findings highlight persistent gender disparities and structural workforce challenges in Japanese neuro-oncology, underscoring the need for institutional strategies to promote sustainable workforce development and gender equity.